Differential Role of PD-1 Expressed by Various Immune and Tumor Cells in the Tumor Immune Microenvironment: Expression, Function, Therapeutic Efficacy, and Resistance to Cancer Immunotherapy - Kim, Myeong Joon; Ha, Sang-Jun (Frontiers in Cell and Developmental Biology, 2021)
In the tumor immune microenvironment (TIME), tumor cells interact with various cells and operate various strategies to avoid antitumor immune responses. These immune escape strategies often make the TIME resistant to cancer immunotherapy. Neutralizing immune escape strategies is necessary to overcome resistance to cancer immunotherapy. Immune checkpoint receptors (ICRs) expressed in effector immune cells inhibit their effector function via direct interaction with immune checkpoint ligands (ICLs) expressed in tumor cells. Therefore, blocking ICRs or ICLs has been developed as a promising cancer immunotherapy by reinvigorating the function of effector immune cells. Among the ICRs, programmed cell death 1 (PD-1) has mainly been antagonized to enhance the survival of human patients with cancer by restoring the function of tumor-infiltrating (TI) CD8+ T cells. It has been demonstrated that PD-1 is expressed not only in TI CD8+ T cells, but also in other TI immune cells and even tumor cells. While PD-1 suppresses the function of TI CD8+ T cells, it is controversial whether PD-1 suppresses or amplifies the suppressive function of TI-suppressive immune cells (e.g., regulatory T cells, tumor-associated macrophages, and myeloid cells). There is also controversy regarding the role of tumor-expressing PD-1. Therefore, a precise understanding of the expression pattern and function of PD-1 in each cell subset is important for improving the efficacy of cancer immunotherapy. Here, we review the differential role of PD-1 expressed by various TI immune cells and tumor cells. We focused on how cell-type-specific ablation or blockade of PD-1 affects tumor growth in a murine tumor model. Furthermore, we will also describe how the blockade of PD-1 acts on TI immune cells in human patients with cancer.